2020
DOI: 10.1158/0008-5472.can-19-3923
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Stem Cell Dependence on Glutaminase Reveals a Metabolic Vulnerability through the Amino Acid Deprivation Response Pathway

Abstract: Cancer cells can metabolize glutamine to replenish TCA cycle intermediates, leading to a dependence on glutaminolysis for cell survival. However, a mechanistic understanding of the role that glutamine metabolism has on the survival of glioblastoma (GBM) brain tumor stem cells (BTSC) has not yet been elucidated. Here we report that, across a panel of 19 glioblastoma BTSC lines, inhibition of glutaminase (GLS) showed a variable response from complete blockade of cell growth to absolute resistance. Surprisingly, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Its synthesis and degradation are part of the glutamate/glutamine cycle. Due to its role as a neurotransmitter, Glu is constantly released from neurons and its uptake by astrocytes at the neuronal synapse is essential for maintaining normal brain function [ 65 , 66 ]. After its release, Glu is taken up by astrocytes, where it is converted to Gln and released again [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its synthesis and degradation are part of the glutamate/glutamine cycle. Due to its role as a neurotransmitter, Glu is constantly released from neurons and its uptake by astrocytes at the neuronal synapse is essential for maintaining normal brain function [ 65 , 66 ]. After its release, Glu is taken up by astrocytes, where it is converted to Gln and released again [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dependency of glioblastoma and tumor-associated endothelial cells on glycolysis, but also glutaminolysis for energy production, opens further opportunities to reduce tumor-related angiogenesis (Seyfried et al, 2015;Artzi et al, 2017). Glutamine consumption is often increased in malignant tumors and the inhibition of intracellular glutaminase (GLS) activity -which converts glutamine into glutamate -has been shown to reduce proliferation and angiogenesis of tumor cells of different origin (Draoui et al, 2017;Zhao et al, 2017;Bruntz et al, 2019;Restall et al, 2020). Recent studies have demonstrated that Se-induced inhibition of glutaminolysis in malignant cells resulted from the suppression of GLS activity (Zhao et al, 2017;Bruntz et al, 2019).…”
Section: Selenium and Angiogenesismentioning
confidence: 99%
“…Compound 968 and CB-839 were able to successfully dampen the in vitro clonogenicity of glioblastoma stem-like cells (GSCs) in neurosphere colonies, resulting in a significant reduction in the number of GSCs [ 148 ]. Further investigation of the mechanism was performed by another study, which showed that the sensitivity to CB-839 in GSCs was not due to the contribution of glutaminolysis to the TCA cycle; rather, the sensitivity was brought on by reduced intracellular glutamate, which led to the amino acid deprivation response (AADR) [ 149 ]. Continuing this line of research, a modification of the CB-839 delivery route was developed by loading the drug into PEGylated gold nanoparticles with conjugated CD133 aptamers (Au-PEG-CD133-CB-839) [ 150 ].…”
Section: Glutaminolysis-specific Intervention For Cscsmentioning
confidence: 99%